The Effect of Consumer Friendship and Completeness of Building Material Products on the Decision of Buying In-terest in the Prima Baja Aek Tapa Rantauprapat Building Materials Store - Nur Awaliyah Suci; Jeni Sukmal; Erni Manja Hasibuan (Pusat Riset dan Inovasi Nasional, 2025)
The aim of this research is to determine whether or not there is a significant influence of consumer friendliness and the completeness of building material products on purchasing interest decisions at the Prima Baja building materials shop AEK Tapa Rantauprapat. The research uses quantitative methods and an associative causality approach. The data collection technique used is through observation and interviews. The sample in this research was 88 respondents or consumers. The sampling technique is simple random sampling with a significance of 1%. The data analysis technique uses statistical techniques/SPSS by carrying out validity and reliability tests then for questionnaires and multiple linear regression analysis with the T Test and F Test to prove the hypothesis. The research results show that there is a close and significant influence of consumer friendliness on purchasing interest decisions, there is no close and significant influence of product completeness on purchasing interest decisions. The influence of consumer friendliness and product completeness is 70.7% and the remaining 29.3% is influenced by other factors and variables.